Practice of Modified Safety Measures for Covid-19 Adopted by Dental Health Care Providers and Barriers Faced by Them: Practice of Modified Safety Measures for COVID-19 - Kandhro, Rehmatullah; Naz Memon, Khalida; Parveen Rajpar, Shazia; Talpur, Nida; Nissa, Zobia; Khalid, Qasim (Pakistan Journal of Health Sciences, 2023)
The COVID-19 infection has influenced almost everyone belonging to every walk of life especially dental practitioners are introduced to a higher bet of getting infected because of close contact with such patients. The COVID-19 has put an enormous hassle on clinical benefits system across the globe. The dental practice is to highly needed change in accordance with the new scourge circumstance in order to reduce the risks of SARS-CoV-2 infection transmission. Objective: To investigate practice of modified safety measures by the dentists regarding COVID-19 outbreak. Methods: Descriptive cross-sectional study was conducted among dentists working at Institute of dentistry Liaquat University of Medical and Health Sciences Jamshoro, Dental outpatient department of Hyderabad, and private dental practitioners of Hyderabad city, Pakistan by convenience sampling technique. The analysis of data were conducted using SPSS version 23.0 after adjusting the potential confounders and to analyze association between dentist response and age, gender, and other characteristics by applying Chi-Square test. Results: Most of the dental professionals are scared of developing COVID-19 from a patient or co-worker (83.17%) and are well known about its transmission (93.36%) and use PPE (74.17%). Conclusions: Although having a high valuable level of knowledge and practice, dental practitioners around the world are in a state of anxiety and dread while working in their respective fields due to the COVID-19 pandemic impact on mankind.